Usage of Finite Element Method and iAnalysis of Car Hood Model with Different Material and Speed for Crash Test by using Abaqus Explicit Software in Automotive Application - Dagang, Jimmy Kudi; Mohamed, Norirda; Khalid, Amir (Progress in Engineering Application and Technology, 2021)
In this study, the most important variables like material, speed, and different car hood thickness are studied to analyze the crashworthiness during a collision. This study aims to compare two different types of material aluminium and steel on car hood by different speeds and determine the response of elements in terms of hood deformation, energy absorbed, Von-Mises stresses, kinetic energy, and internal energy and strain energy of hood. Next is to investigate the potential of Abaqus/- Explicit as the tool to simulate vehicle crashes into a rigid wall in general. Two types of material were used and evaluated as hood materials. The results indicated that it is possible to simulate the full-scale crash using Abaqus/-Explicit. Different Impact velocity of the vehicle was, 13889 mm/s (50 km/h), 20833 mm/s (75 km/h), 27778 mm/s (100 km/h). The response of elements was observed in terms of Hood deformation, Von-Mises stresses, kinetic energy, energy absorption, internal energy and strain energy therein were presented and discussed. The conclusion from the results is that Abaqus/Explicit is a suitable finite element software for simulating crashes. From the analysis, the hood material aluminium has good ability compared to steel at various speed.